Le courage qu’il faut aux rivières (Emmanuelle Favier) : trans·former le genre et la sexualité - Camélia Paquette (Genre, Sexualité et Société)
Le courage qu’il faut aux rivières by Emmanuelle Favier, published in 2017, depicts the love bond between two masculine women, a relationship that seems unintelligible where one woman performs gender to escape marriage while the other is forced by her father to be a man. Sexuality is present throughout their journey, inseparable from their identity quest for recognition. At times the quest is positive, a way and a space of (re)taking possession of oneself through an erotic gaze, thourgh onanism that reminds the body of the female organs or thourgh restorative sexual partnership. Yet the quest is also negative, a demonstration of patriarchal repression in the face of a violated heteronormative system, especially through rape. Throughout the story, sexuality thus becomes the milestones of self-affirmation towards transidentity.